Prevalence and clinical characteristics of serum neuronal cell surface antibodies in first-episode psychosis: a case-control study. (January 2017) - Lennox, Belinda R; Palmer-Cooper, Emma C; Pollak, Thomas; Hainsworth, Jane; Marks, Jacqui; Jacobson, Leslie; Lang, Bethan; Fox, Hannah; Ferry, Berne; Scoriels, Linda; Crowley, Hannah; Jones, Peter B; et al.
Summary: Background: Psychosis is a common presenting feature in antibody-mediated encephalitis, for which prompt recognition and treatment usually leads to remission. We aimed to investigate whether people with circumscribed schizophrenia-like illnesses have such antibodies—especially antibodies against the N-methyl-D-aspartate receptor (NMDAR)—more commonly than do healthy controls. Methods: We recruited patients aged 14–35 years presenting to any of 35 mental health services sites across England with first-episode psychosis, less than 6 weeks of treatment with antipsychotic medication, and a score of 4 or more on at least one selected Positive and Negative Syndrome Scale (PANSS) item. Patients and controls provided venous blood samples. We completed standardised symptom rating scales (PANSS, ACE-III, GAF) at baseline, and tested serum samples for antibodies against NMDAR, LGI1, CASPR2, the GABAA receptor, and the AMPA receptor using live cell-based assays. Treating clinicians assessed outcomes of ICD diagnosis and functioning (GAF) at 6 months. We included healthy controls from the general population, recruited as part of another study in Cambridge, UK. Findings: Between Feb 1, 2013, and Aug 31, 2014, we enrolled 228 patients with first-episode psychosis and 105 healthy controls. 20 (9%) of 228 patients had serum antibodies against one or more of the neuronal cell surface antibodies compared with four (4%) of 105 controls (unadjusted odds ratio 2·4, 95% CI 0·8–7·3). These associations remained non-significant when adjusted for current cigarette smoking, alcohol consumption, and illicit drug use. Seven (3%) patients had NMDAR antibodies compared with no controls (p=0·0204). The other antibodies did not differ between groups. Antibody-positive patients had lower PANSS positive, PANSS total, and catatonia scores than did antibody-negative patients. Patients had comparable scores on other PANSS items, ACE-III, and GAF at baseline, with no difference in outcomes at 6 months. Interpretation: Some patients with first-episode psychosis had antibodies against NMDAR that might be relevant to their illness, but did not differ from patients without NMDAR antibodies in clinical characteristics. Our study suggests that the only way to detect patients with these potentially pathogenic antibodies is to screen all patients with first-episode psychosis at first presentation. Funding: Medical Research Council.